2010
DOI: 10.1016/j.ajo.2009.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Genetic Diagnosis for Stargardt Disease

Abstract: Purpose To report the first use of in vitro fertilization (IVF) and preimplantation genetic diagnosis to achieve an unaffected pregnancy in an autosomal-recessive retinal dystrophy. Design Case report. Methods An affected male with Stargardt disease and his carrier wife underwent IVF. Embryos obtained by intracytoplasmic sperm injection underwent single-cell DNA testing via polymerase chain reaction and restriction enzyme analysis to detect the presence of ABCA4 mutant alleles. Embryos were diagnosed as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
0
7
0
1
Order By: Relevance
“…Support was less strong for genetic testing as part of reproductive planning. The use of preimplantation genetic diagnosis to achieve an unaffected pregnancy has been reported in cases of recessive Stargardt disease, severe RP and X-linked retinoschisis4 15 and prenatal testing has also been reported for Leber congenital amaurosis 3. Sizeable proportions of the current sample supported the use of genetic testing for reproductive planning purposes: 65% of participants supported carrier status testing, and 52% and 47% supported preimplantation and prenatal genetic testing for inherited retinal disease, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Support was less strong for genetic testing as part of reproductive planning. The use of preimplantation genetic diagnosis to achieve an unaffected pregnancy has been reported in cases of recessive Stargardt disease, severe RP and X-linked retinoschisis4 15 and prenatal testing has also been reported for Leber congenital amaurosis 3. Sizeable proportions of the current sample supported the use of genetic testing for reproductive planning purposes: 65% of participants supported carrier status testing, and 52% and 47% supported preimplantation and prenatal genetic testing for inherited retinal disease, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…The rationale to perform WES in proband 2 was that the partner had Stargardt disease (MIM #248200, caused by recessive mutations in ABCA4) [18] and the reason for initiating molecular genetic investigation was that the couple sought preconception counseling. As it has been reported that the frequency of ABCA4 mutation carriers in a general population may be relatively high [19], arguably warranting preconception screening in partners of patients with ABCA4 related disease [20], we decided that WES was more cost-effective than setting up conventional Sanger sequencing for the detection of CRB1 and ABCA4 coding region variants.…”
Section: Resultsmentioning
confidence: 99%
“…The well-known variability of clinical expression of BEST1 mutations within and between families, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] together with our findings on the extremely variable expressivity of subclinical Best VMD, are of particular interest in the era of assisted reproduction. 40 Because prenatal diagnosis is difficult to offer in a disease with a variable expressivity and with known subclinical forms, preimplantation diagnosis is questionable, especially in individuals with subclinical forms, which have a risk to transmit the disease to descendants.…”
Section: Discussionmentioning
confidence: 99%